Bioactive Compound Profiling and Antioxidant Activity of Phytelephas tenuicaulis and Other Amazonian Fruits - Elena Coyago-Cruz; David Valenzuela; Aida Guachamin; Gabriela Méndez; HEREDIA MOYA, JORGE HUMBERTO; Edwin Vera (MDPI AG, 2024)
The Amazon region is home to many plant species, many of which have not been studied. The objective was to evaluate the physicochemical properties, bioactive compounds, and antioxidant activity of Phytelephas tenuicalis (tintiuk), Grias neuberthii (apai), Euterpe oleracea (acai), and Mauritia flexuosa (brown moriche). Physicochemical analyses were carried out on fresh fruit from local markets. Bioactive compounds (carotenoids, phenolics, vitamin C, and organic acids) were quantified in the freeze-dried pulp by rapid-resolution liquid chromatography (RRLC), and antioxidant activity was determined by ABTS and DPPH assays. The results showed high soluble solids (10.7 °Brix) and ascorbic acid (67.3 mg/100 g DW) in tintiuk; β-carotene (63.4 mg/100 g DW) and malic acid (19.6 g/100 g DW) in brown moriche; quercetin (944.2 mg/100 g DW) and antioxidant activity by ABTS (6.7 mmol ET/100 g DW) in apai; and citric acid (2.1 g/100 g DW) in acai. These results indicate interesting bioactive properties that could increase the consumption of these fruits nationally and internationally, benefiting local farmers and stimulating the development of new products in functional food, medicine, and cosmetics.
Keywords: antioxidants; ascorbic acid; bioactive compounds; carotenoids; functional foods; organic acid; phenolics